Hidden culprit: Unveiling recurrent chest pain masked by myocardial bridge - Anil Dev Gopalakrishna; Mamatha Tittamegalapalya Ramalingaiah (Asian Journal of Medical Sciences, 2025)
A 52-year-old female presented to us in the emergency medicine department with a history of recurrent left precordial and retrosternal chest pain of dull aching type but not radiating to the left arm or neck, sometimes accompanied by sweating. These episodes had been occurring for 3 years, with each episode lasting for more than 1 h. The patient had a history of diabetes and hypertension and was on medications. She was evaluated outside; oesophago-gastro-duodenoscopy was done. It showed normal. She was on analgesics and on proton pump inhibitor. Our patient had persistent chest pain and was admitted for the same symptoms. After serial electrocardiogram (ECG) and serial troponin levels were noted to be normal. Hence, coronary angiogram was done. It showed a myocardial bridge lesion in the left anterior descending artery. It is a rare cause of chest pain, often we tend to narrow diagnosis once ECG and trop t negative. Significant obstruction can lead to myocardial ischemia, arrhythmia, and even sudden cardiac death. Early consideration in the working diagnosis enables early detection and treatment. This case report aims to enhance clinical decision making, improve patient outcome, and stimulate further research in this intriguing field.